Transcriptomic Analysis of Skin Tissue Reveals Molecular Mechanisms of Thermal Adaptation in Cold-Exposed Lambs - Mengyu Feng; Kaixi Ji; Yutao Li; Pâmela Almeida Alexandre; Dan Jiao; Yanping Liang; Xia Du; Xindong Cheng; Huitong Zhou; Jon G. H. Hickford; Guo Yang (Animals)
Cold stress impacts lamb mortality, welfare, and productivity. Wool and skin insulate lambs, but the mechanisms underlying their response to colder environments remain unclear. Shorn lambs (n = 20) of similar age (8 months), of the Hulunbuir (n = 10; average 34.5 ± 0.70 kg) and Hu (n = 10; average 34.9 ± 0.79 kg) breeds, were raised at the Ecological and Agricultural Experimental Station, Gaolan, Gansu Province, People’s Republic of China (36°13″ N, 103°47″ E), at an altitude of 1780 m above sea level. These lambs were divided into four equal groups: Hulunbuir at −20 °C (HB−20), Hulunbuir at 15 °C (HB+15), Hu at −20 °C (HU−20), and Hu at 15 °C (HU+15). The groups were maintained at these temperatures in temperature-controlled facilities for 38 days. Skin tissues were analyzed with transcriptome sequencing, and selected wool and physiological traits were assessed. The HB−20 lambs had greater wool length growth (1.8 ± 0.13 vs. 1.0 ± 0.46 cm, p < 0.001) and epidermis thickness (20.0 ± 1.20 vs. 14.6 ± 0.87 μm, p = 0.006) but lower hair follicle density (33.6 ± 2.11 vs. 42.7 ± 3.06 per mm2, p = 0.041), rectal temperature (38.1 ± 0.10 vs. 38.8 ± 0.04 °C, p < 0.001), and respiratory rate (15.5 ± 1.08 vs. 24.0 ± 1.89 breaths/min, p = 0.004), compared to the HB+15 lambs. Similar differences in these traits were observed with the Hu lambs at the two temperatures. Transcriptome analyses revealed the activation of pathways related to immune and endocrine systems, signal transduction, and development and regeneration, irrespective of breed at −20 °C. The TNF signaling pathway and osteoclast differentiation may play roles in cold adaptation, as they are associated with differentially expressed genes (DEGs) identified in the Hulunbuir lambs, as well as shared DEGs between both breeds. This study revealed physiological and molecular differences in lambs exposed to lower temperatures and suggests potential targets for improving cold tolerance, welfare, and productivity.